Light and oxygen facilitating the directly treatment food wastewater and poly-β-hydroxybutyrate, 5-aminolevulinic acid, pigment productions by Rubrivivax gelatinosus. (8th March 2023) - Xu, Xiaohan; Gao, Ziqing; Wu, Xian; Chen, Xi
Abstract: Rubrivivax gelatinosus has the advantage of using wastewater to realize biomass recovery. However, they still cannot be applied large scale because they cannot directly treat the wastewater containing macromolecular organics. Thus, this article investigated the effects of light–oxygen conditions on R. gelatinosus by directly recycling wastewater containing macromolecular organics to produce biomass, poly- β -hydroxybutyrate (PHB), 5-aminolevulinic acid (5-ALA), and pigment. Results showed that R. gelatinosus directly treated the macromolecule organic (soybean protein and starch) wastewaters and achieved biomass recovery under light–anaerobic and light–micro-oxygen in six conditions. Chemical oxygen demand, protein, and starch removals for two wastewaters all reached above 70%. Renewable bio-resources such as biomass, PHB, 5-ALA, and pigment production were 10 times the initial content. Theoretical analysis indicated that light activated the synthesis of protease and amylase. However, oxygen concentration decided the number of enzymes. When oxygen was at micro-oxygen or anaerobic, the aforementioned expression and synthesis were conducted. In summary, this study expanded the viewpoint ignored by traditional theory. It was realized that R. gelatinosus directly treated wastewater and accumulated nutrients (biomass, PHB, pigment, and 5-ALA) for recycling, which reduced the secondary pollution of excess sludge into the environment. HIGHLIGHTS: This study expands the traditional theory of Rubrivivax gelatinosus directly un-degrading wastewater. R. gelatinosus had the potential to directly degrade wastewaters, and recycled biomass under light–anaerobic. Light affected the synthesis of protease and amylase in R. gelatinosus . Oxygen concentration affected the number of enzymes. Graphical Abstract